A Semantic Analysis Of English-To-Indonesian Literary Translation - Dorand, Pietra; Roihan, Muhamad (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
The globalization of postcolonial literature has made translation a bridge of accessibility for Indonesian readers to access iconic works by authors such as Meyer and Twain, with semantic analysis ensuring that the emotional and ideological essence of the source text remains intact for the sake of literacy and cultural diplomacy. Developing an integrated semantic framework for the translation of English literature into Indonesian through multidimensional comparative analysis, filling research gaps, improving equivalence accuracy to 85%, and supporting the training of hybrid translators to enrich the accessibility of global literature locally. The research employs a Systematic Literature Review (SLR) designed to systematically identify, evaluate, and synthesize relevant empirical evidence, providing a comprehensive, objective overview of the state-of-the-art, identifying knowledge gaps through a transparent, structured protocol that minimizes bias. Three categories were analyzed: cultural aspects demonstrated that transference and domestication reduced meaning distortion by 35%, with the translator acting as a mediator to balance fidelity and relevance; semantic strategies identified that a hybrid approach increased accuracy by 80% through DeepL’s contextual corrections and nine allegorical paraphrasing strategies; translation of specific linguistic elements such as modals, interjections, and mental processes achieves 75–85% equivalence through contextual substitution and annotation, though persistent challenges regarding subjective nuances and emotional intensity require a micro-linguistic approach. This study concludes that cultural negotiation is essential for cross-cultural semantic equivalence, with hybrid strategies minimizing distortion and enhancing accessibility; innovative semantic strategies, including corrective AI, are crucial for resolving ambiguity and improving precision; and the adaptation of linguistic elements through contextual annotation is vital for preserving the authentic emotional nuances of the narrative.